Improving Safety in Catheter Ablation for Atrial Fibrillation: A Prospective Study of the Use of Ultrasound to Guide Vascular Access. (2nd April 2014) - WYNN, GARETH J.; HAQ, IRAM; HUNG, JOHN; BONNETT, LAURA J.; LEWIS, GAVIN; WEBBER, MATTHEW; WAKTARE, JOHAN E.P.; MODI, SIMON; SNOWDON, RICHARD L.; HALL, MARK C.S.; TODD, DERICK M.; GUPTA, DHIRAJ
Vascular Ultrasound for AFA Introduction The most frequent complications of AF ablation (AFA) are related to vascular access, but there is little evidence as to how these can be minimized. Methods Consecutive patients undergoing AFA at a high‐volume center received either standard care (Group S) or routine ultrasound‐guided vascular access (Group U). Vascular complications were assessed before hospital discharge and by means of postal questionnaire 1 month later. Outcome measures were BARC 2+ bleeding complications, postprocedural pain, and prolonged bruising. Results Patients in Group S (n = 146) and U (n = 163) were well matched at baseline. Follow‐up questionnaires were received from 92.6%. Patients in Group U were significantly less likely to have a BARC 2+ bleed, 10.4% versus 19.9% P = 0.02, were less likely to suffer groin pain after discharge (27.1% vs. 42.8%; P = 0.006) and were less likely to experience prolonged local bruising (21.5% vs. 40.4%; P = 0.001). Multivariable logistic regression analysis revealed a significant association of vascular complications with nonultrasound guided access (OR 3.12 95%CI 1.54–5.34; P = 0.003) and increasing age (OR 1.05 95%CI 1.01–1.09; P = 0.02). Conclusion Routine use of ultrasound‐guided vascular access for AFA is associated with a significant reduction in bleeding complications, postprocedural pain, and prolonged bruising when compared to standard care.